VARIATION WITHIN BREWING YEAST POPULATIONS - Brindley, Stephanie (2019)
Harvesting yeast at the end of fermentation and using it to reinoculate a subsequent fermentation (serial repitching) is unique to the brewing industry. Despite its prevalence, this process can come at a cost; reusing yeast can negatively impact product and process consistency. In particular, fermentation completion time variability is an issue. In some cases, this variation is explained by differences in wort composition, raw materials or yeast viability, however it may also be the result of population shifts within the genome or phenome. Although much is already known about factors which impact the brewing yeast genome, phenotypic diversity within brewing yeast strains has not previously been explored. In this thesis I provide data to suggest that phenotypic heterogeneity (i.e. non-genetic variation) is evident in a range of brewing yeast populations, based on their sensitivity to brewery related stress factors. Initially, the propensity for brewing strains to yield variants was explored in the lager yeast strains W34/70, CBS1174 and CBS1260 and the ale strains M2 and NCYC1332 using DNA fingerprinting techniques and giant colony morphology plating. Subsequently, phenotypic heterogeneity was assessed by determining resistance to key stress factors: ethanol, osmotic (sorbitol) and oxidative (H2O2) stress. Populations exposed to ethanol stress displayed the greatest differences in heterogeneity, while osmotic and oxidative stress elicited a more conserved response. Of all of the strains, the lager yeast W34/70 was identified as being particularly phenotypically diverse. Further investigation into the cellular response of this strain to prolonged exposure to ethanol found evidence of a bet-hedging strategy in the lager yeast W34/70, suggesting that the process of serial repitching could potentially select for sub-populations of cells thereby decreasing the populations overall heterogeneity. This theory was examined by fermenting W34/70 under low level ethanol stress over an extended period of time. After 18 days the population became more homogeneous in nature comprising mainly of highly resistant cells. However, upon removing the primary selective agent, ethanol, the measurement of heterogeneity proved that the investment in the switch was not permanent as after one normal, small scale fermentation the heterogeneity was found to be shifting back towards that of the control sample. The relationship between phenotypic heterogeneity and stress factor indicates that this concept is extremely complex in industrial systems. Nevertheless, the data presented here sheds new light on the potential root causes of viability loss, and why some strains are more suitable for certain fermentations.